2018
DOI: 10.18203/2319-2003.ijbcp20183936
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire based survey on knowledge, attitude and behaviour of antibiotic usage and resistance among undergraduates in South Indian teaching hospital

Abstract: Background: Antibiotic resistance has become a global threat in the field of medicine. Multiple causes like antibiotic abuse, irrational usage of antibiotics, over the counter availability of antibiotics etc., have been put forth as culprit leading to antibiotic resistance. The present study aims at evaluating the knowledge, attitude and behaviour of antibiotic usage and resistance among undergraduates in South Indian teaching hospital.Methods: A cross-sectional, questionnaire-based survey conducted in undergr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…A study in southern India revealed that only a small group of students realised that antibiotics could cause secondary infections by killing good gut bacteria (6). Other studies reported that around 10% to 15% of the participants could not differentiate between antibiotics and other medications such as aspirin and paracetamol, anti-inflammatory, antipyretic and analgesic drugs (6,7). However, the current study discovered that most participants could distinguish common antibiotics like penicillin and amoxicillin from other types of medications.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…A study in southern India revealed that only a small group of students realised that antibiotics could cause secondary infections by killing good gut bacteria (6). Other studies reported that around 10% to 15% of the participants could not differentiate between antibiotics and other medications such as aspirin and paracetamol, anti-inflammatory, antipyretic and analgesic drugs (6,7). However, the current study discovered that most participants could distinguish common antibiotics like penicillin and amoxicillin from other types of medications.…”
Section: Discussioncontrasting
confidence: 62%
“…Regarding antibiotic side effects, 92.3% of the participants were unaware of antibiotics' side effects, such as disrupting the patient's normal microflora. A study in southern India revealed that only a small group of students realised that antibiotics could cause secondary infections by killing good gut bacteria (6). Other studies reported that around 10% to 15% of the participants could not differentiate between antibiotics and other medications such as aspirin and paracetamol, anti-inflammatory, antipyretic and analgesic drugs (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a high expectation in regard to use vaccine that sparks our immune response and helping our body fights off and remember the germ so it can attack it if the germ ever invades again [30]. About 75% respondents answered that 'antibiotics should be used only prescribed by doctors', a comparable result to that found in a study conducted in South Indian teaching hospital (67%) [31]. In the current study most respondents (96.3%) intended to establish a course on "Rational use of antibiotics" at the university level.…”
Section: Discussionmentioning
confidence: 77%
“…With regard to practices towards antibiotic use, nearly half of respondents (48.3%) stated that "They don't stop the use of antibiotics as soon as they experience better' a lower percentage than was found in studies conducted in South Indian teaching hospital (53.4%) [31]. But in comparison with same studies conducted in South Indian teaching hospital [31, a higher percentage of practice was found regarding that 'They don't ask to the doctor to dispense antibiotics for common cold'.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, ABR training activities should not be limited to the outreach of students. Investments should be allocated to develop awareness campaigns that educate society about the causes and consequences of drug resistance [15]. This investment could improve societal attitudes toward antibiotic consumption, especially in India, where most of the population is young.…”
Section: Introductionmentioning
confidence: 99%